Suramin prevents the development of diabetic kidney disease by inhibiting NLRP3 inflammasome activation in KK‐Ay mice - Kaori Oda; Satoshi Miyamoto; Ryo Kodera; Jun Wada; Kenichi Shikata (Journal of Diabetes Investigation, 2023)
Abstract Aims/Introduction Nucleotide‐binding oligomerization domain‐like receptor family pyrin domain containing 3 (NLRP3) inflammasomes produce IL‐18 upon being activated by various stimuli via the P2 receptors. Previously, we showed that serum and urine IL‐18 levels are positively associated with albuminuria in patients with type 2 diabetes, indicating the involvement of inflammasome activation in the pathogenesis of diabetic kidney disease (DKD). In the present study, we investigated whether the administration of suramin, a nonselective antagonist of the P2 receptors, protects diabetic KK.Cg‐Ay/TaJcl (KK‐Ay) mice against DKD progression. Materials and Methods Suramin or saline was administered i.p. to KK‐Ay and C57BL/6J mice once every 2 weeks for a period of 8 weeks. Mouse mesangial cells (MMCs) were stimulated with ATP in the presence or absence of suramin. Results Suramin treatment significantly suppressed the increase in the urinary albumin‐to‐creatinine ratio, glomerular hypertrophy, mesangial matrix expansion, and glomerular fibrosis in KK‐Ay mice. Suramin also suppressed the upregulation of NLRP3 inflammasome‐related genes and proteins in the renal cortex of KK‐Ay mice. P2X4 and P2X7 receptors were significantly upregulated in the isolated glomeruli of KK‐Ay mice and mainly distributed in the glomerular mesangial cells of KK‐Ay mice. Although neither ATP nor suramin affected NLRP3 expression in MMCs, suramin inhibited ATP‐induced NLRP3 complex formation and the downstream expression of caspase‐1 and IL‐18 in MMCs. Conclusions These results suggest that the NLRP3 inflammasome is activated in a diabetic kidney and that inhibition of the NLRP3 inflammasome with suramin protects against the progression of early stage DKD.